Databases for the study of entrepreneurship - Katz, Jerome A. (Advances in entrepreneurship, firm emergence and growth ;, 2001)
This work contains papers reporting on the structure, utilization and analytic concerns arising from the use of the major datasets in small business and entrepreneurship research including: the National Federation of Independent Businesses surveys; US Small Business Administration datasets; the General Social Survey; the US Current Population Surveys; the Panel Study of Income Dynamics; and, many others from around the world.